Total Matrix Ca2+ Modulates Ca2+ Efflux via the Ca2+/H+ Exchanger in Cardiac Mitochondria - Natarajan, Gayathri K.; Glait, Lyall; Mishra, Jyotsna; Stowe, David F.; Camara, Amadou K. S.; Kwok, Wai-Meng (Frontiers in Physiology, 2020)
Mitochondrial Ca2+ handling is accomplished by balancing Ca2+ uptake, primarily via the Ru360-sensitive mitochondrial calcium uniporter (MCU), Ca2+ buffering in the matrix and Ca2+ efflux mainly via Ca2+ ion exchangers, such as the Na+/Ca2+ exchanger (NCLX) and the Ca2+/H+ exchanger (CHE). The mechanism of CHE in cardiac mitochondria is not well-understood and its contribution to matrix Ca2+ regulation is thought to be negligible, despite higher expression of the putative CHE protein, LETM1, compared to hepatic mitochondria. In this study, Ca2+ efflux via the CHE was investigated in isolated rat cardiac mitochondria and permabilized H9c2 cells. Mitochondria were exposed to (a) increasing matrix Ca2+ load via repetitive application of a finite CaCl2 bolus to the external medium and (b) change in the pH gradient across the inner mitochondrial membrane (IMM). Ca2+ efflux at different matrix Ca2+ loads was revealed by inhibiting Ca2+ uptake or reuptake with Ru360 after increasing number of CaCl2 boluses. In Na+-free experimental buffer and with Ca2+ uptake inhibited, the rate of Ca2+ efflux and steady-state free matrix Ca2+ [mCa2+]ss increased as the number of administered CaCl2 boluses increased. ADP and cyclosporine A (CsA), which are known to increase Ca2+ buffering while maintaining a constant [mCa2+]ss, decreased the rate of Ca2+ efflux via the CHE, with a significantly greater decrease in the presence of ADP. ADP also increased Ca2+ buffering rate and decreased [mCa2+]ss. A change in the pH of the external medium to a more acidic value from 7.15 to 6.8 6.9 caused a 2-fold increase in the Ca2+ efflux rate, while an alkaline change in pH from 7.15 to 7.4 7.5 did not change the Ca2+ efflux rate. In addition, CHE activation was associated with membrane depolarization. Targeted transient knockdown of LETM1 in permeabilized H9c2 cells modulated Ca2+ efflux. The results indicate that Ca2+ efflux via the CHE in cardiac mitochondria is modulated by acidic buffer pH and by total matrix Ca2+. A mechanism is proposed whereby activation of CHE is sensitive to changes in both the matrix Ca2+ buffering system and the matrix free Ca2+ concentration.